2015
DOI: 10.3897/zookeys.505.9021
|View full text |Cite
|
Sign up to set email alerts
|

Availability of eleven species names of Eupelmus (Hymenoptera, Eupelmidae) proposed in Al khatib et al. (2014)

Abstract: This paper is an addendum for the availability of the names of 11 new species proposed in Al khatib et al. (2014).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 1 publication
0
19
0
4
Order By: Relevance
“…Ratzeburg, 1844† Eupelmus spongipartus Förster, 1860 Prior to the recognition of additional species in the 'E. urozonus complex' (Al khatib et al, 2015), specimens with a relatively long ovipositor sheath (about as long as the marginal vein) were identified as E. annulatus and those with a shorter sheath as E. urozonus. Eupelmus azureus, however, has a long sheath like E. annulatus; the two species are readily separable on the sculpturation of the scrobal depression which is mainly smooth and shiny in E. azureus but largely reticulate in E. annulatus (Al khatib et al, 2015;Gibson & Fusu, 2016 Gibson & Fusu (2016) identified E. confusus from Mallorca.…”
Section: Eupelmus (Eupelmus) Annulatus Nees 1834mentioning
confidence: 99%
See 4 more Smart Citations
“…Ratzeburg, 1844† Eupelmus spongipartus Förster, 1860 Prior to the recognition of additional species in the 'E. urozonus complex' (Al khatib et al, 2015), specimens with a relatively long ovipositor sheath (about as long as the marginal vein) were identified as E. annulatus and those with a shorter sheath as E. urozonus. Eupelmus azureus, however, has a long sheath like E. annulatus; the two species are readily separable on the sculpturation of the scrobal depression which is mainly smooth and shiny in E. azureus but largely reticulate in E. annulatus (Al khatib et al, 2015;Gibson & Fusu, 2016 Gibson & Fusu (2016) identified E. confusus from Mallorca.…”
Section: Eupelmus (Eupelmus) Annulatus Nees 1834mentioning
confidence: 99%
“…Al khatib, 2015 † This is the species associated with Ephedra in the Monegros region of Zaragoza, recorded under 'Eupelmus sp.' as a parasitoid of Blascoa ephedrae Askew (Hym., Pteromalidae) in the seeds (Askew & Blasco-Zumeta, 1997) and as a primary and secondary parasitoid of the gall-forming Eurytoma gallephedrae Askew (Askew & Blasco-Zumeta, 1998 (1♀ 27.vi.2009, Juncosa).…”
Section: Eupelmus (Eupelmus) Azureusmentioning
confidence: 99%
See 3 more Smart Citations